The impact of aerobic and balance exercises on anxiety and dizziness in post-COVID-19 patients: a randomised clinical trial - Mabrouk, Mohamed Ibrahim; Abdalbary, Sahar Ahmed; Abdelmonem, Asmaa Foad; Mohamed Abdelhakiem, Nadia; Anwar Ahmed, Alaa; Mostafa Gelany, Fathia; Abd El Rahim, Ahmed A. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Examine how aerobic exercises, relaxation techniques, and balance exercises aﬀect patients’ anxiety and diz-ziness post-COVID-19 patients.Methods. Thirty participants post-COVID-19, complaining of anxiety and dizziness, aged 45–65 years, of both sexes, selected from the outpatient clinic of our hospital, were enrolled in the study after a COVID-19 infection. Treatment sessions were 3 times weekly for 4 weeks, and the patients were treated separately in group therapy. The 15 patients in group A were given aerobic, balancing, and relaxation techniques. The 15 patients in the control group (group B) were given only relaxation exercises. Assess-ments of the two groups were completed both before and after the course of treatment by the Hamilton Anxiety Scale (HAMA) and the Berg Balance Scale. Respiratory function was also assessed using maximum voluntary ventilation.Results. There were signiﬁcant diﬀerences between the two groups after the treatment. The mean values of the HAMA after treatment were 17.2 ± 1.7 and 21.7 ± 1.4 in groups A and B, respectively. After treatment, the mean values of the Berg Balance Scale were 26.7 ± 5.7 and 22.2 ± 3.6 in groups A and B, respectively. The mean values of maximum voluntary ventilation were 117.2 ± 16.7 and 108.1 ± 16.3 in groups A and B, respectively. Both groups showed a signiﬁcant decrease in anxiety and dizziness and a signiﬁcant increase in maximum voluntary ventilation at the end of the 4 weeks of the training program. Participants in group A showed a signiﬁcantly greater decrease in anxiety and dizziness and a signiﬁcantly greater increase in maximum volun-tary ventilation (p < 0.05) after the training program.Conclusions. Ultimately, it can be said that aerobic exercises, balance exercises, and relaxation techniques can raise maximal voluntary breathing and lessen anxiety and dizziness in post-COVID patients. Therefore, it might be regarded as a successful, secure, cost-eﬀective, and eﬃcient supplementary treatment method for lowering anxiety and vertigo in COVID-19 patients.
Keywords: aerobic exercises; balance exercises; anxiety disorder; dizziness